CHAT-S study protocol: A randomized controlled trial of a health insurance literacy education program for young adult cancer survivors - Mary Killela; Cindy A. Turner; Amy Chevrier; Monique Stefanou; Perla L. Vaca Lopez; Heydon K. Kaddas; Karely M. van Thiel Berghuijs; Echo L. Warner; Giselle K. Perez; Austin R. Waters; Douglas B. Fair; Richard E. Nelson; et al. (Preventive Oncology & Epidemiology)
Background: Health insurance education could mitigate financial toxicity experienced by young adult (YA) cancer survivors by increasing confidence when navigating cancer care costs. This paper describes the protocol in a randomized controlled trial (RCT) to test a virtual patient navigation program designed to help YA cancer survivors understand their health insurance.Methods: This is a two-arm, multi-site (Huntsman Cancer Institute, Intermountain Health) RCT wherein intervention participants receive four sessions with a patient navigator and a booklet on insurance; usual care receives the booklet. We will enroll 300 YA cancer survivors (n = 200 intervention; n = 100 usual care) diagnosed with breast, testicular, lymphoma, sarcoma, colorectal, melanoma, or thyroid cancer between the ages of 26 and 39, who have completed treatment in the past two years. All participants will complete three surveys: enrollment, 6 months, and 12 months; medical records/insurance claims data will be collected out to 18-month follow-up. The primary outcomes include improvement in health insurance literacy and financial toxicity at 6 months. Secondary outcomes include adherence to cancer surveillance guidelines at 18 months. We will also conduct cost-effectiveness and budget impact analyses.Discussion: Anticipated results from this trial could identify key information that YA cancer survivors need to improve health insurance literacy and survivorship care.Trial registration: ClinicalTrials.gov identifier: NCT05829070. Registered on April 25, 2023.